2021
DOI: 10.1002/adom.202100104
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Induced Stark Effect and Reversible Photoluminescence Quenching in Inorganic Perovskite Nanocrystals

Abstract: Inorganic perovskite nanocrystals (NCs) have demonstrated a number of unique optical and electronic properties for optoelectronic applications. However, the physical properties of these nanostructures, such as the dynamics of charge carriers on different timescales and their effect on the optical recombination of carriers, are not yet fully understood. This work reports on a slow (>1 s) reversible quenching of the NC photoluminescence due to a light‐induced Stark effect involving defects on the surface of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…[23,24] A complex excitonic structure was uncovered in perovskites and individual excitonic transitions were probed in a magnetic field of up to 60 T. [25,26] Meanwhile, charge transport studies in high magnetic fields revealed unique quantum phenomena in graphene, such as a room temperature quantum Hall effect [24] and a giant quantum Hall effect plateau. [27] To date, the properties of perovskite-graphene heterostructures in high magnetic fields remain largely unknown and could enable a fundamental understanding of the complicated charge transfer mechanisms observed in this system, [19,20] hence advancing their applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23,24] A complex excitonic structure was uncovered in perovskites and individual excitonic transitions were probed in a magnetic field of up to 60 T. [25,26] Meanwhile, charge transport studies in high magnetic fields revealed unique quantum phenomena in graphene, such as a room temperature quantum Hall effect [24] and a giant quantum Hall effect plateau. [27] To date, the properties of perovskite-graphene heterostructures in high magnetic fields remain largely unknown and could enable a fundamental understanding of the complicated charge transfer mechanisms observed in this system, [19,20] hence advancing their applications.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of these devices, such as their response time, is affected by the slow, >1 s, redistribution of charge between the graphene layer and PNCs under light and/or electrostatic gating, [18,19] leading to the accumulation of a large amount of charge in the PNCs (7 × 10 12 cm −2 [19] ). This phenomenon can induce a range of interesting physical phenomena, such as an optically induced Stark effect, [20] large hysteresis on the gate voltage dependence of the graphene resistance, [19] and enhancement of the photoresponsivity. [21,22] However, to fully exploit the potential of perovskite/graphene structures, a comprehensive understanding of their properties is still needed.…”
mentioning
confidence: 99%
“…[61,62] Consequently, a blueshift in the PL peak is observed from the remaining CsPbBr 3 material in the NC core, instead of the redshifts reported in the literature for other types of mixed-halide perovskite NCs. [63,64] Of special note is that some of the surface iodide anions could be lost via the molecular formation and the subsequent sublimation processes, [15,42,65] resulting in the small amount of residual CsPbBr 3 emission after the majority of segregated CsPbBr 1.2 I 1.8 NCs have been converted to the mixed phase (see, e.g., the bottom panels in Figure 1c,d). This unexpected loss of iodine elements becomes more obvious when the CsPbBr 1.2 I 1.8 NCs are illuminated by the laser light for longer times (see Figure S15, Supporting Information, for the energy dispersive X-ray spectroscopy measurements), which can be suppressed by various strategies such as the growth of a PbSO 4 shell on the NC surface.…”
Section: Resultsmentioning
confidence: 99%
“…The instability of PQDSCs may be attributed to the structural instability of CsPbI 3 PQDs caused by the smaller size of Cs + compared to MA + and FA + , as well as their high sensitivity to environmental factors (such as humidity, heat, light, etc.) arising from their inherent ionic nature and dynamic surface. …”
Section: Introductionmentioning
confidence: 99%